src64 and tec29 are required for microfilament contraction during Drosophila cellularization. - Thomas, J.H.; Wieschaus, E. (Development, 2004)
Formation of the Drosophila cellular blastoderm involves both membrane invagination and cytoskeletal regulation. Mutations in src64 and tec29 reveal a novel role for these genes in controlling contraction of the actin-myosin microfilament ring during this process. Although membrane invagination still proceeds in mutant embryos, its depth is not uniform, and basal closure of the cells does not occur during late cellularization. Double-mutant analysis between scraps, a mutation in anillin that eliminates microfilament rings, and bottleneck suggests that microfilaments can still contract even though they are not organized into rings. However, the failure of rings to contract in the src64 bottleneck double mutant suggests that src64 is required for microfilament ring contraction even in the absence of Bottleneck protein. Our results suggest that src64-dependent microfilament ring contraction is resisted by Bottleneck to create tension and coordinate membrane invagination during early cellularization. The absence of Bottleneck during late cellularization allows src64-dependent microfilament ring constriction to drive basal closure.